PEMBUATAN PUPUK ORGANIK DAN PESTISIDA NABATI DI DESA PEMATANG JOHAR MELALUI KEGIATAN KKNT - Nurhajijah Nurhajijah; Risnawati Risnawati; Wan Arfiani Barus; Rini Susanti; Dwiky Reza Sihotang; Hafiz Nur Khadafi Sipayung; Riris Nadya Syafrillia Gurning (Universitas Mataram, 2023)
Pematang johar Village or what is known today as the Rice Field Tourism Village is one of the villages in Deli Serdang district. This village is one of the rice storage villages in Deli Serdang district. Most of the residents in the village of Pematang Johar work as farmers including rice farmers. In increasing the productivity of rice plants, it is necessary to carry out learning or guidance related to cultivation in agriculture. One of the supporting factors in increasing productivity is related to fertilization and the use of pesticides or plant pest control. The purpose of the activity of making organic fertilizers and vegetable pesticides is the application of technology in sustainable agriculture. In addition, this activity provides benefits to the community, especially farmers from Pematang Johar Village, Dusun XV, to understand the manufacture of organic fertilizers and vegetable pesticides. So that people, especially farmers, know about the differences between organic farming and inorganic farming. The results to be achieved in the activity of making organic fertilizers and vegetable pesticides to increase the ability of the women of Pematang Johar Dusun XV Village, although initially the mothers of Pematang Johar Dusun XV Village had difficulty understanding the tricks we provided but the enthusiasm from the village mothers Pematang Johar Dusun XV is very strong so that we are still enthusiastic about providing an understanding of this vegetable pesticide.